Enhancing Maternal and Infant Health: Improving Healthcare Access through Cultural Sensitivity and Community Engagement in Tigalingga, Dairi Regency - Amri, Siskawati; Simbolon, Roma Sinta (Law and Economics, 2023)
This research investigates the state of maternal and infant health in Tigalingga, Dairi Regency, emphasizing the significance of reducing mortality rates among mothers and infants in this underserved community. Employing a mixed-method approach, the study combines quantitative analysis and qualitative insights to understand the multifaceted landscape of healthcare challenges. Utilizing regional health records, interviews, and community engagement, the study unveils critical disparities, cultural influences, and barriers to healthcare access. The findings showcase higher-than-desired maternal and infant mortality rates, underscoring the urgency for targeted interventions. The Health Assistance Program, a focal point of the research, demonstrates promising outcomes in reducing mortality rates. The program's success is attributed to improved healthcare access, culturally sensitive interventions, and community engagement. Recommendations derived from the study advocate for sustained efforts in healthcare infrastructure development, enhanced community involvement, and cultural adaptation in healthcare initiatives. The implications of the research extend to public health policy, emphasizing the importance of equitable healthcare access, culturally competent interventions, and community-driven strategies. The research underscores the critical need for tailored healthcare interventions, respecting cultural practices and addressing healthcare disparities, to improve the health outcomes of mothers and infants in Tigalingga. The findings serve as a foundation for informed decision-making and the development of targeted interventions not only within the region but also for similar vulnerable communities globally